The Effect of the Application of Class Based Storage Method on Increasing the Utility in The Warehouse at CV. Bachtiar Jaya Plastic - Tiaraningtya, Dyah Ayu; Sutandi, Sutandi; Purnaya, I. Nyoman (Jurnal Logistik Indonesia, 2022)
This study aims to determine how big the influence of the application of the Class- based Storage Method on the Improvement of Utilities in the Waste Warehouse in CV. Bachtiar Jaya Plastic. By applying the Class-Based Storage method, the benefits in the warehouse can be more optimal, the speed in the storage process and the accuracy in managing the warehouse to meet consumer needs. The research methodology used is descriptive quantitative research method, with samples in this study as many as 30 performances using the Non Probability Sampling Technique, namely Saturated Sampling. The results of this study indicate that Class-Based Storage has an effect on Warehouse Utility. based on the results of the t-test obtained the value of t-count > t-table (5,282>2,048). It can be concluded that H0 is rejected and H1 is accepted, or there is an influence between the application of the Class Based Storage Method on increasing the utility in the warehouse.